Análises bioquímicas e biomecânicas do metabolismo ósseo de ratas ovariectomizadas - Duarte, Nathália Tuany [UNESP] (2010)
Estrogen plays an important role in both reproductive and non-reproductive tissues; it influences pubertal growth, regulates bone maturation, and maintains bone mass in women and in men after puberty. In menopausal women the estrogen is associated with various diseases, which include bone resorption. Today, medicine is the attempt to make the hormone replacement, but without causing further damage to the body. The goal of the present study was to systematically to define the dose-response effect of estrogen on bone of ovariectomized rats. This study used Wistar rats (6 months) intact and ovariectomized (OVX). After 15 days of OVX, were inserted pellets containing corn oil or estradiol with 100, 200 or 300 g of 17- estradiol, during 60 days. After this period and under anesthesia (xylazine-4mg/kg; ketamine-40mg/Kg), blood was collected of jugular vein and then, the animals were sacrificed by the excess of anesthetic for removal of the femurs. The blood was centrifuged and plasma stored in a freezer for subsequent biochemical determination of calcium, phosphorus and alkaline phosphatase. The femurs were analyzed mechanically bending three-point (shaft) and axial compression applies to the condyle. The results showed no statistically significant difference in the analysis of the middle third of the experimental groups. The compression test of the femoral head showed that the group treated with 100 g of estradiol had a higher compressive strength than the group treated with 200 g of estradiol. The plasma concentration of calcium was similar between groups, but the phosphorus was significantly lower in the OVX group treated with 100 g of estradiol and alkaline phosphatase in animals that received 200 g of estradiol.These results show that the concentration of 100 g of estradiol administered to female rats after estropausa triggers significant effects on bone structures, mainly in trabecular bone